Entrepreneurship experiential learning through simulation game / Nurul Hayani Abd Rahman ... [et al.] - Abd Rahman, Nurul Hayani; Mansor, Roseamilda; Shafie, Nani Ilyana; Umar, Azli; Mohd Shariff, Balqis; Abd Rahman, Nurul Fazila (2020)
In the current gaming landscape, simulated skills and competencies vary according to the challenges present in a game. Offering different level of challenges, The Young Entrepreneur Network (YENT) is a simulation game for entrepreneurship experiential learning. This creative simulation game aims to introduce participants to various components such as entrepreneurship decision-making, venture management, financial management, and personal development. YENT's first phase was designed to provide information related to the services sector available in Malaysia. As the largest contributor to the country's economy, the services sector consists of wholesale and retail trade, information and communication, and finance and insurance. In the first phase of entrepreneurial decision-making, knowledge of a sector's capacity is useful as it helps an entrepreneur moves on to the next phase.